First Detailed Anatomical Study of Bonobos Reveals Intra-Specific Variations and Exposes Just-So Stories of Human Evolution, Bipedalism, and Tool Use - Diogo, Rui (Frontiers in Ecology and Evolution, 2018)
Just-so stories are prominent in human evolution literature because of our tendency to create simple progressionist narratives about our 'special' place in nature, despite the fact that these stories are almost exclusively based on hard tissue data. How can we be so certain about the evolution of human facial communication, bipedalism, tool use, or speech without detailed knowledge of the internal anatomy of, for instance, one of the two extant species more closely related to us, the bonobos? Here I show how many of these stories now become obsolete, after such a comprehensive knowledge on the anatomy of bonobos and other primates is finally put together. Each and every muscle that has been long accepted to be 'uniquely human' and to provide 'crucial singular functional adaptations' for our bipedalism, tool use and/or vocal/facial communication, is actually present as an intra-specific variant or even as normal phenotype in bonobos and/or other apes.